The post-secular turn and its consequences for the practice of science - Kaczmarek, Jerzy (Człowiek i Społeczeństwo, 2016)
In this article, the author tackles the post-secular turnaround in the context of practising science, and as such how this manner of thinking has affected how science, its tasks and its practical activity is perceived by those practising it. Initially two fundamental concepts are discussed, namely secularisation and post-secularism – their pedigree and ways in which they are expressed. The article deals later with issues related to the presence of religious references in the natural sciences, as well as the possibilities of utilising the natural sciences in religion and theology. Consequently, the area of issues embraced by the new scientific sub-discipline known as the theology of science is discussed. The article then addresses the discourse regarding the presence of theology and religion in sociology, and refers to the conceptions of such sociologists as P. Rieff, K. Flanagan, Z. Krasnodębski, E. Hałas and K.T. Konecki. Finally, it indicates possible further consequences of post-secular thinking in the field of sociology, and relates the current post-secular turn to Nikolai Berdyaev’s concept of the New Middle Ages.